Heterogeneous red-white discoloration of the nail bed and distal onycholysis in a patient with COVID-19 - Demir, B.; Yuksel, E. I.; Cicek, D.; Turkoglu, S. (Wiley, 2021)
[Abstract Not Available]
Keywords: Lines